Sax's dangerous properties of industrial materials - Lewis, Richard J., Sr., 1939-2018 (John Wiley & Sons, Inc., 2012)
"Since its inception in the early 1950's, this book has become the "bible" for those who need to evaluate the hazard of substances used in commerce. The book contains extensive data on approximately 28,000 substances. It is designed to fill the information needs of professionals who must work with and evaluate the hazards of chemicals"-- Provided by publisher.
Originally authored by N. Irving Sax and published in 1951 under title Handbook of dangerous materials; revised in 1957 as Dangerous properties of industrial materials; editions 2-7 of Dangerous properties of industrial materials (published 1963-1989) also authored by Sax; editions 8-11 authored by Richard J. Lewis, Sr. (published 1992-2004) have title Sax's dangerous properties of industrial materials.
Keywords: Hazardous substances -- Handbooks, manuals, etc.; elektronické knihy; electronic books